2004
DOI: 10.4049/jimmunol.173.5.3155
|View full text |Cite
|
Sign up to set email alerts
|

IL-15Rα Is a Negative Regulator of TCR-Activated Proliferation in CD4+ T Cells

Abstract: Although IL-15 is known to be a T cell growth factor, the function in T cells of IL-15Rα, its high affinity receptor, remains unclear. We found that murine IL-15Rα−/− CD4+ T cells hyperproliferated in response to TCR stimulation, in vitro and in vivo, and displayed a lower TCR activation threshold than wild-type CD4+ T cells. TCR-induced activation of Zap70 and of the phospholipase C-γ1-NFATp, Ras-ERK-c-Fos, and Rac-JNK-c-Jun pathways was all augmented in IL-15Rα−/− CD4+ T cells. This in turn led to earlier IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…This reported phenomenon represents a general theme irrespective of the applied antigens (KLH or OVA) or immunization routes (s.c. or i.p.) used in priming and was not due to the potential defects of IL‐15Rα KO CD4 + T cells 9, 27. This is supported by the observation that replacement of CD45.1 + OT‐II CD4 + T cells in the priming of CD45.2 + mice also resulted in IL‐10 overproduction.…”
Section: Discussionmentioning
confidence: 64%
“…This reported phenomenon represents a general theme irrespective of the applied antigens (KLH or OVA) or immunization routes (s.c. or i.p.) used in priming and was not due to the potential defects of IL‐15Rα KO CD4 + T cells 9, 27. This is supported by the observation that replacement of CD45.1 + OT‐II CD4 + T cells in the priming of CD45.2 + mice also resulted in IL‐10 overproduction.…”
Section: Discussionmentioning
confidence: 64%
“…A previous report indicated that IL-15Rα is a negative regulator of TCR-stimulated proliferation of CD4 + T cells [68]. If so, blocking IL-15 should enhance proliferation of TCR-stimulated CD4 + T cells.…”
Section: Resultsmentioning
confidence: 96%
“…During AAD, IL‐15 −/− mice also showed increased numbers of CD4 + T cells and B cells in the spleen and BAL, and decreased numbers of CD8 + T cells in the spleen and lung, relative to WT controls. IL‐15Rα is a negative regulator of proliferation of CD4 + T cells . In the absence of IL‐15 signalling, CD4 + T cells hyperproliferate when stimulated via the T cell receptor.…”
Section: Discussionmentioning
confidence: 99%